2022
DOI: 10.1016/j.cgh.2021.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Global Prevalence of Metabolic Dysfunction-Associated Fatty Liver Disease in Overweight or Obese Adults

Abstract: BACKGROUND & AIMS:Metabolic dysfunction-associated fatty liver disease (MAFLD) is a new terminology updated from non-alcoholic fatty liver disease (NAFLD). In this study, we aim to estimate the global prevalence of MAFLD specifically in overweight and obese adults from the general population by performing a systematic review and meta-analysis through mining the existing epidemiological data on fatty liver disease. METHODS:We searched Medline, Embase, Web of Science, Cochrane and google scholar database from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 32 publications
(38 reference statements)
3
83
0
5
Order By: Relevance
“…A recently published systematic review and meta-analysis showed that the estimated global prevalence of MAFLD in overweight and obese adults was 50.7%, with a higher prevalence in men (59.0%) than women (47.5%) [ 51 ]. The pooled estimated prevalence of comorbidities was 19.7% and 57.5% for T2DM and metabolic syndrome, respectively [ 51 ].…”
Section: The Evidence To Support the Change In Terminology From Nafld To Mafldmentioning
confidence: 99%
“…A recently published systematic review and meta-analysis showed that the estimated global prevalence of MAFLD in overweight and obese adults was 50.7%, with a higher prevalence in men (59.0%) than women (47.5%) [ 51 ]. The pooled estimated prevalence of comorbidities was 19.7% and 57.5% for T2DM and metabolic syndrome, respectively [ 51 ].…”
Section: The Evidence To Support the Change In Terminology From Nafld To Mafldmentioning
confidence: 99%
“…(2021 г. ), обобщивший результаты 116 исследований (n=2 667 052), показал, что глобальная распространенность НАЖБП у взрослых лиц с избыточной массой тела и ожирением составляет 50,7% (95% ДИ 46,9-54,4) [58]. Согласно метаанализу L. Li и соавт.…”
Section: заболевания печениunclassified
“…Recently, a new definition was suggested for NAFLD, namely metabolic dysfunction-associated fatty liver disease (MAFLD) [ 2 ]. The prevalence of MAFLD among obese adults worldwide is 50.7%, with 95% CI 46.9–54.4 [ 3 ], relatively higher in men (59.0%, 95% CI 52.0–65.6) than women (47.5%, 95% CI 40.7–54.5). NAFLD is tightly associated with obesity, diabetes, and metabolic syndromes [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%